The null identities for boundary operators in the (2, 2p + 1) minimal gravity. (22nd February 2020) - Ishiki, Goro; Muraki, Hisayoshi; Rim, Chaiho
Abstract: By using the matrix model representation, we show that correlation numbers of boundary-changing operators (BCOs) in $(2, 2p+1)$ minimal Liouville gravity satisfy some identities, which we call the null identities. These identities enable us to express the correlation numbers of BCOs in terms of those of boundary-preserving operators. We also discuss a physical implication of the null identities as the manifestation of the boundary interaction.